A rare cause of ascites in a newborn: Posterior urethral valve - Gurgoze, Metin Kaya; Yildirmaz, Serap; Dogan, Yasar; Ozel, Kerem; Gun, Onder (Wiley-Blackwell Publishing, Inc, 2010)
[Abstract Not Available]
Keywords: Urinary Ascites